Extracranial injections of botulinum neurotoxin type A inhibit intracranial meningeal nociceptors' responses to stimulation of TRPV1 and TRPA1 channels: Are we getting closer to solving this puzzle?. (August 2016) - Zhang, XiChun; Strassman, Andrew M; Novack, Victor; Brin, Mitchell F; Burstein, Rami
Background: Administration of onabotulinumtoxinA (BoNT-A) to peripheral tissues outside the calvaria reduces the number of days chronic migraine patients experience headache. Because the headache phase of a migraine attack, especially those preceded by aura, is thought to involve activation of meningeal nociceptors by endogenous stimuli such as changes in intracranial pressure (i.e. mechanical) or chemical irritants that appear in the meninges as a result of a yet-to-be-discovered sequence of molecular/cellular events triggered by the aura, we sought to determine whether extracranial injections of BoNT-A alter the chemosensitivity of meningeal nociceptors to stimulation of their intracranial receptive fields. Material and methods: Using electrophysiological techniques, we identified 161 C- and 135 Aδ-meningeal nociceptors in rats and determined their mechanical response threshold and responsiveness to chemical stimulation of their dural receptive fields with TRPV1 and TRPA1 agonists seven days after BoNT-A administration to different extracranial sites. Two paradigms were compared: distribution of 5 U BoNT-A to the lambdoid and sagittal sutures alone, and 1.25 U to the sutures and 3.75 U to the temporalis and trapezius muscles. Results: Seven days after it was administered to tissues outside the calvaria, BoNT-A inhibited responses of C-type meningeal nociceptors to stimulation of their intracranial dural receptive fields with the TRPV1 agonist capsaicin and the TRPA1 agonist mustard oil. BoNT-A inhibition of responses to capsaicin was more effective when the entire dose was injected along the suture lines than when it was injected into muscles and sutures. As in our previous study, BoNT-A had no effect on non-noxious mechanosensitivity of C-fibers or on responsiveness of Aδ-fibers to mechanical and chemical stimulation. Discussion: This study demonstrates that extracranial administration of BoNT-A suppresses meningeal nociceptors' responses to stimulation of their intracranial dural receptive fields with capsaicin and mustard oil. The findings suggest that surface expression of TRPV1 and TRPA1 channels in dural nerve endings of meningeal nociceptors is reduced seven days after extracranial administration of BoNT-A. In the context of chronic migraine, reduced sensitivity to molecules that activate meningeal nociceptors through the TRPV1 and TRPA1 channels can be important for BoNT-A's ability to act as a prophylactic.